Apikasi Jasa Jahit Pakaian Berbasis mobile dengan Teknologi Location Based Services dan Metode SMART - Susandri Susandri; Hidaya Spitri; Lusiana Lusiana; Koko Harianto (Jurnal Inovtek Polbeng Seri Informatika, 2020)
Clothing tailor services are available in every region, but so far customers have to come to tailors to sew clothes. There is no application that makes it easy for service users and tailors to interact with each other. In order to help customers and tailors interact, a sewing service order system must be created. This research uses Location Based Service (LBS) technology as a guide for home and tailor locations the Simple Multi-Attribute Rating Techniqui (SMART) method for ranking the quality of tailor services. The steps used in this study consist of system analysis, system design and implementation. This research has produced applications that can facilitate customers and tailors to interact with each other use mobile technology